1992
DOI: 10.1016/s0022-5347(17)37287-7
|View full text |Cite
|
Sign up to set email alerts
|

p53, c-erbB-2 and the Epidermal Growth Factor Receptor in the Benign and Malignant Prostate

Abstract: Expression of the p53, the epidermal growth factor receptor (c-erbB-1) and c-erbB-2 protein was studied in 34 men with benign prostatic hyperplasia and 29 men with locally advanced prostate cancer by means of an immuno-histochemical method. Strong staining for p53 was found in five of 29 prostate cancers (17%; mean 21% +/- 7% of malignant cells stained in the positive tumours), but no staining was found in benign prostatic hyperplasia (p less than 0.05). On the other hand, the epithelium in benign glands was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
1
3

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(57 citation statements)
references
References 29 publications
5
48
1
3
Order By: Relevance
“…The accumulation of p53 progression, compared with 12 of 21 with p53-negative protein has been reported previously in 11-20% of tumours who progressed (P=0.02). In addition, patients localized prostatic adenocarcinomas and 56% of primary positive for p53 had a significantly shorter mean (95%CI) tumours that had metastasized, using a variety of antitime to progression, at 21 (14-29) months, than those bodies including BP53-12-1 [19], CM1 [9] and PAb240 negative for p53, at 33 (24-42) months (P=0.038; [20]. The higher proportion of tumours with positive Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of p53 progression, compared with 12 of 21 with p53-negative protein has been reported previously in 11-20% of tumours who progressed (P=0.02). In addition, patients localized prostatic adenocarcinomas and 56% of primary positive for p53 had a significantly shorter mean (95%CI) tumours that had metastasized, using a variety of antitime to progression, at 21 (14-29) months, than those bodies including BP53-12-1 [19], CM1 [9] and PAb240 negative for p53, at 33 (24-42) months (P=0.038; [20]. The higher proportion of tumours with positive Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both Ware et al (1991) and Mellon et al (1992) used fresh material and found c-erbB-2 protein expression in 71% and in 21%, respectively, while McCann et al (1990) did not observe c-erbB-2 protein expression in formalin-fixed tissue. Ware et al (1991) also compared fresh and formalin-fixed tissue, and found that formalin fixation significantly reduced the c-erbB-2 protein immunoreactivity, which may explain the rather low c-erbB-2 protein reactivity (1.5%) in our series.…”
Section: Statisticsmentioning
confidence: 97%
“…The biological significance of p53 overexpression is not yet established, but most authors agree that p53 protein expression occurs relatively late in neoplastic transformation. In prostate cancer nuclear p53 protein accumulation has been correlated with histological grade (Mellon et al, 1992), tumour progression (Berner et al, 1993) and DNA ploidy (Visakorpi et al, 1992). Van Veldhuizen et al (1993) recently reported a predominant cytoplasmic staining pattern in 79% of a series of prostatic carcinomas.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunopositivity for c-erbB-2 oncoprotein among large number of patients with prostate cancer and its correlation with higher tumour grade and stage, high S-phase and aneuploidy has been reported by several investigators (41)(42)(43)(44). Contrary to this, some studies did not observe any significant relationship between c-erbB-2 immunoexpression and tumour stage or grade (45).…”
mentioning
confidence: 89%